(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
This study aims to produce gluten-free biscuits, with appropriate sensory and nutritional characteristics, to be used as functional food suitable for celiac disease patients, by mixing corn flour and sweet lupine in certain proportions. Four biscuit formulas were prepared, three of which contain 60% by weight of corn and sweet lupine flour in the following proportions, respectively (50%, 10%-40%, 20%-30%,30%), and the fourth formula contains 60% wheat flour. Carrot pomace was used at 15% in all four formulas. The sensory characteristics of the four formulas were evaluated with the participation of 30 tasters of different age groups, and compared with commercial gluten-free biscuits from the local market. The results showed that the best sensory formula was the first formula consisting of 50% corn flour and 10% lupine flour. The nutritional value of the prepared biscuits with the best sensory properties was studied, and the percentage of nutrients available in it such as moisture, ash, fat, fiber, protein, and digestible carbohydrates were determined, and they were, respectively, 2.40%, 2.67%, 12.46%, 2.86%, 7.86%,and 71.66%. The amount of gluten in biscuits prepared using the portable Nima device and the immunoassay device was determined to be higher than 20 and 40 ppm, respectively. Despite the good nutritional and sensory value of the prepared biscuit, it was not free from gluten despite all the precautionary measures that were taken, which may be due to the contamination of lupine and corn grains used in preparing the biscuit with gluten-containing materials, either during cultivation and harvesting in the fields and farms, or in places of sale, which requires that the raw materials used in the composition of such products be grown and prepared in their own facilities to prevent contamination.